PENYERBUKAN TERKENDALI DAN UJI KETURUNAN FULL-SIB JATI (Tectona grandis L.f.) - , SUGI PURWANTA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The aims of this research were 1) to find out the success rate of control pollination in teak